REORIENTASI MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DAN DERADIKALISASI AGAMA - Fatah Syukur (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
Islamic religious education in schools substantively had a very important role. In accordance with the mandate of the Law on National Education System, religious education should be provided to learners at all levels of education. Religious education was expected not only to provide knowledge of religion, but also build the personality character of the students using religious values taught. Through quantitative research, this study examined the implementation of Islamic religious education in schools with the research problems: is there any correlation with religious observance, and any other factors that affect the behavior of religion? How does the orientation of Islamic religious educationin schools? The results showed that Islamic education is not positively correlated to the level of religious observance. Similarly, differences in men and women are not correlated to the level of religious observance. Therefore, there will be necessary reorientation of religious education in schools.